What sexual harassment in Zentropa tells us about cultural policy post-Weinstein - Sorensen, Inge (Feminist Media Studies, 2018)
Publisher: Routledge _eprint: https://doi.org/10.1080/14680777.2018.1456165
Keywords: Irina

Hard facts, soft measures: Gender, quality and inequality debates in Danish film and television in the 2010s - Redvall, Eva Novrup; Sørensen, Inge Ejbye (Journal of Scandinavian Cinema, 2018)
Abstract This article investigates discussions about gender, quality and equality in Danish film and television in the 2010s. Contrary to Sweden, where gender diversity has been part of public debate and formal screen policy since the 2000s, there was little discussion of gender in the Danish screen industry until the Danish Film Institute (DFI) began focusing on diversity as a priority area before the Film Strategy for 2015–18. The article analyses how both DFI and industry players have continuously argued against gender quotas, instead opting for soft measures such as ‘gender declarations’ and initiatives to raise awareness. One of these initiatives was a manifesto, ManusFestet, that used humour to raise questions about gender representation on-screen. The article discusses how a balance between hard facts and soft measures seems to be experienced as a constructive way forward, as long as this combination does in fact facilitate the intended change.
Publisher: Intellect
Keywords: Irina